2011
DOI: 10.1142/s0218271811020676
|View full text |Cite
|
Sign up to set email alerts
|

On the Meaning of General Covariance and the Relevance of Observers in General Relativity

Abstract: Since the appearance of General Relativity, its intrinsec general covariance has been very often misinterpreted as implying that physically meaningful quantitities (and conclusions extracted from the theory) have to be absolutely independent on observers. This incorrect point of view is sometimes expressed by discarding the very concept of observer in the structure and applications of the theory. As we shall stress in this essay, through some examples, the concept of observer is as essential to General Relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…On the basis of the orthogonal splitting approach of the Riemann tensor studied by Bel [ 47 ] and followed by [ 48 , 49 , 50 , 51 , 52 , 53 ], we shall calculate structure scalars in metric gravity. We shall use terminologies with minor changes as that utilized in [ 48 ].…”
Section: Orthogonal Splitting Of Curvature Tensorsmentioning
confidence: 99%
“…On the basis of the orthogonal splitting approach of the Riemann tensor studied by Bel [ 47 ] and followed by [ 48 , 49 , 50 , 51 , 52 , 53 ], we shall calculate structure scalars in metric gravity. We shall use terminologies with minor changes as that utilized in [ 48 ].…”
Section: Orthogonal Splitting Of Curvature Tensorsmentioning
confidence: 99%
“…This equation has directly relate Y T to the effective matter variables and Tolman mass function. It is well-known from the working of Herrera et al [54,55] and Yousaf et al [56][57][58] that Y T has been involved in the evolutionary equation of the expansion scalar which is widely known as Raychaudhuri equation. Equation (57) suggests that m T could be used to define the Raychaudhuri equation even in f (R, T, Q) gravity.…”
Section: The Orthogonal Splitting Of the Riemann Tensormentioning
confidence: 99%
“…This expression explicitly relates Y T to the matter variables with modified corrections and Tolman mass function in f (R, T, Q) theory. Herrera et al [63,64] and Yousaf et al [65][66][67] shown the involvement of Y T in the evolutionary equation for the expansion scalar, commonly known as Raychaudhuri equation. Thus, Eq.…”
Section: The Mass Functionmentioning
confidence: 99%